Effect and Mechanism of Swimming Exercise Preconditioning on Neurological Function of Mice with Intracerebral Hemorrhage - LI Yongxu; LIN Libin; LU Taotao; WEI Wei; LIN Zhicheng; XUE Xiehua (康复学报)
ObjectiveTo observe the effect of swimming exercise preconditioning on neurological function and expression levels of brain derived neurotrophic factor (BDNF), serine-threonine kinase (Akt) and peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) proteins in perihematoma tissues of mice with intracerebral hemorrhage (ICH).MethodsA total of 60 male C57BL/6 mice were randomly divided into sham group, ICH 7 d group, SEP+ICH 7 d group (preconditioning group 1), ICH 14 d group and SEP+ICH 14 d group (preconditioning group 2), with 12 cases in each group. The preconditioning group 1 and preconditioning group 2 were preconditioned with swimming exercise for four weeks. After four weeks, ICH model was induced by stereotactic injection of collagenase type Ⅳ into the right striatum of mice in the ICH 7 d group, the preconditioning group 1, the ICH 14 d group and the preconditioning group 2, while normal saline was injected into the sham group. Neurological function was evaluated and neurometabolites were detected on the 7th day after modeling in the ICH 7 d group and the preconditioning group 1, and on the 14th day after modeling in the sham group, the ICH 14 d group and the preconditioning group 2. Modified neurological severity score (mNSS) and Y maze method were used to detect the neurological function; open field test was used to detect the motor function. Magnetic resonance spectroscopy (MRS) was used to analyze the relative metabolism levels of creatine (Cr), choline (Cho), N-acetylaspartate (NAA), myo-inositol (MI), and lactate (Lac) in surrounding tissues of hematoma. Western blot was used to detect the expression levels of BDNF, p-Akt/Akt and PGC-1α.Results(1) Neurological function and motor function: compared with the sham group, the mNSS score in the ICH 7 d group and the ICH 14 d group significantly increased, and the total movement distance, the average velocity of the open field test and correct alternation rate of Y maze significantly decreased (P<0.05). Compared with the ICH 7 d group, mNSS in the preconditioning group 1 and the preconditioning group 2 significantly decreased, and the total movement distance, the average velocity of the open field test and correct alternation rate of Y maze significantly increased (P<0.05). Compared with the ICH 14 d group, mNSS score in the preconditioning group 1 and the preconditioning group 2 significantly decreased, and the total movement distance, the average velocity of the open field test and correct alternation rate of Y maze significantly increased (P<0.05). (2) Neurometabolism: compared with the sham group, NAA/Cr and Cho/Cr in the ICH 7 d group and the ICH 14 d group significantly decreased (P<0.05), and MI/Cr significantly increased (P<0.05). Compared with the ICH 7 d group and the ICH 14 d group, NAA/Cr and Cho/Cr in the preconditioning group 1 and the preconditioning group 2 significantly increased (P<0.05), and MI/Cr and Lac/Cr significantly decreased (P<0.05). Compared with the preconditioning group 1, there were no significant differences in NAA/Cr, Cho/Cr, MI/Cr and Lac/Cr in the preconditioning group 2 (P>0.05). (3) The expression levels of BDNF, p-Akt and PGC-1α: compared with the sham group, the expression of BDNF in the ICH 7 d group significantly decreased (P<0.05), there were no significant difference in p-Akt/Akt and PGC-1α in the ICH 7 d group and the ICH 14 d group (P>0.05). Compared with the ICH 7 d group, the expression levels of BDNF and PGC-1α in the preconditioning group 1 significantly increased (P<0.05), there was no significant differences in p-Akt/Akt protein (P>0.05). Compared with the ICH 14 d group, the expression of p-Akt/Akt protein in the preconditioning group 2 significantly increased (P<0.05), there were no significant difference in BDNF and PGC-1α. Compared with the preconditioning group 1, there were no significant difference in expression of BDNF and PGC-1α in the preconditioning group 2 (P>0.05), the expression of p-Akt/Akt significantly increased (P<0.05).ConclusionSwimming exercise preconditioning contributes to the recovery of neurological function and the improvement of neurological metabolism around hematoma in ICH mice, which may be related to the upregulation of BDNF, p-Akt/Akt and PGC-1α proteins.